ANALISIS PENGARUH LINGKUNGAN PEMASARAN INTERNET, KARAKTERISTIK PRODUK, KEPERCAYAAN, DAN PROMOSI TERHADAP PERILAKU PEMBELIAN ONLINE TIKET PESAWAT LION AIR DI SURABAYA - WIDYAYA, NICO BUDI (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Internet marketing environment has the distinction has been made between interactivity and interactivity engines. The importance of the characteristics of the products in the online business stems from the fact that the image online store has some fundamental differences from the traditional shops of trust is crucial because it helps manage complexity, help develop the capacity of action, improve collaboration and enhance the learning capabilities of the organization. Promotion is one part of a series of marketing activities. Promotional activities are all efforts undertaken to introduce a product seller to prospective customers and persuade them to buy, as well as remind consumers to take back old repeated purchases using the internet Experience is very important for a consumer. When a consumer is satisfied with her experience using the internet and using the (consume) products then they will revisit the same website to make a purchase. To that end, the study will provide a more in-depth study about the influence of internet marketing environment, product characteristics, trust, and promotions, to conduct online purchases behavior. In this study used is the conclusive research on the study of experimental or causal research. Retrieval technique of sampling used is non probability sampling. The type of method used is the purposive sampling. The sample used was 150 people consumers of Lion Air. Data were collected using a questionnaire. Analysis of technique used was multiple linear regression with the help of the program SPSS. The results of this analysis indicate that the environment of internet marketing, product characteristics, trust, and promotion has significant effects against online purchase behavior.